Nontrivial Existence in Transparent Intensional Logic - Miloš Kosterec (European Journal of Analytic Philosophy, 2024)
The paper analyses the validity of arguments supporting the assumption of a constant universe of individuals over all possible worlds within Transparent Intensional Logic. These arguments, proposed by Tichý, enjoy widespread acceptance among researchers working within the system. However, upon closer examination, this paper demonstrates several weaknesses in the argumentation, suggesting that there is an open possibility to incorporate a variable universe of individuals even in models within this system.